Al-Jassas’s Legal Tafsir: A Rational-Fiqh Analysis of Ahkam al-Quran - Siregar, Muhammad Sururi Alfajri Wannahar; Siregar, Dema (El-Rusyd, 2025)
This study examines the legal exegesis of Abu Bakr Ahmad ibn Ali al-Razi al-Jassas’s as presented in his monumental work Ahkām al-Qurān. The focus of the research is directed toward the fiqh oriented characteristics and the Hanafi rational methodology employed by al-Jassas’s in interpreting legal verses of the Quran. This study adopts a qualitative method using a content analysis approach through an in-depth examination of both primary and secondary sources. The findings reveal that Aḥkam al-Quran represents a rational fiqh based style of Quranic exegesis oriented toward the argumentative derivation of Islamic legal rulings. Al-Jassas’s integrates textual evidence and rational inquiry by combining tafsīr bi al-ma’thūr with the distinctive rational ijtihad of the Hanafi Mahzab. In interpreting legal verses such as Quran 2:262–272, he demonstrates a balanced perspective encompassing moral, social, and legal dimensions, including sincerity in charity, ethics of labor and wages, and charity to non-Muslims as an expression of universal humanism. Al-Jassas’s exegetical approach reflects a methodological commitment to Hanafi legal principles without falling into narrow sectarianism. He views legal exegesis as a dynamic and rational form of intellectual ijtihad aimed at promoting justice and public welfare. In the context of modern Quranic studies, al-Jassas’s method and thought remain relevant for developing a contextual, inclusive, and maqasid al-shariah-oriented legal exegesis.